Penerapan Software Athenaeum Light 8.5 Sebagai Sistem Automasi di Perpustakaan Akademi Teknologi Industri Padang - Sartika, Dilla; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study was: (1) to explain the stages of the process of using the software in the Library Athenaeum Light 8.5 Padang and Industrial Technology Academy and identify the factors that need to be consideration in using the software in the Library Athenaeum Light 8.5 Padang Industrial Technology Academy. Data were collected by means of observation in Padang Industrial Technology Academy Library. Data analysis was done descriptively. Based on data analysis, it can be concluded that the first, the application of library automation is very important because it makes it easy for pemustaka to be used as a search tool and accelerate the work of librarians. Activities using the library automation software in the Library Athenaeum Light 8.5 Padang Industrial Technology Academic namely: (1) management members, (2) circulation, which consists of: (a) borrowing, (b) refund; (c) extension, (3) cataloging , (4) processing, which consists of: (a) collection of data input, b) labeling); 5) search, which consists of: (a) fast find; (b) easy find; (b) detail find; (6) report. Second, the factors that needs to dipertimbangankan in using the software in the Library Athenaeum Light 8.5 Padang Industrial Technology Academy, among others: (1) the availability of human resources, (2) the availability of facilities, (3) availability of computer networks. Keywords:Â Athenaeumk Light 8.5; Library Automation